PENGEMBANGAN FASILITAS WISATA GUNA MENINGKATKAN DAYA TARIK WISATA DI PANTAI AIR BANGIS KABUPATEN PASAMAN BARAT - Safira, Putri; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Air Bangis Beach, a tourist destination in West Pasaman Regency, has significant potential to attract visitors; however, the development of its tourism facilities remains inadequate. This study aims to identify existing tourism facilities, evaluate tourist feedback, and provide recommendations for facility improvement. A mixed-method approach was employed, combining data collection through observations, questionnaires, and in-depth interviews. The findings indicate that facilities such as gazebos, prayer rooms, and toilets need improvements to enhance comfort and cleanliness. Tourists also highlighted the need for additional amenities, including water recreation areas and better-organized local culinary offerings. Recommendations focus on upgrading basic infrastructure, introducing new tourist attractions, and enhancing promotional activities to increase visitor numbers. With proper facility development, Air Bangis Beach is expected to become a premier destination in West Sumatra, contributing to the local economy and strengthening the region's tourism competitiveness. Keywords: Tourism Facility Development, Tourist Attraction, Air Bangis Beach, Local Tourism, Tourism Infrastructur